PLEASE AND POWER STRATEGIES ON STUDENTS’ WRITING COMPETENCY ACROSS TEXT GENRES - Eka Dewi, Putu Mia Sartika (Lingua Scientia, 2020)
The study aimed 1) to verify the main effect of POWER strategy compared to PLEASE strategy on the eighth grade students’ writing competency across text genres at the Junior High School, 2) to verify the effect difference between the two strategies across descriptive text genre, and 2) to verify the effect difference between the two strategies across recount text genre. This research was designed using a quasi-experiment with different text genres. The treatments were repeated in three sessions. The sampled population included all students at the Junior High School, which totaled 60 students. The sample was recruited two classes for comparative treatments. The two groups were selected based on the purpose of comparing between groups. They were assigned to two different group memberships at random basis. A Writing Performance Assessment was administered to collect data. Effects of the two strategies were analyzed using ANOVA and Tukey’s Multiple Comparison Test. The result showed, firstly, a significant effect of PLEASE strategy on the students’ writing competency at SMPN 12 Denpasar. The effect of PLEASE strategy is greater than  POWER strategy (F-ratio = 26.01 ; df = 58; α = 0.05). Secondly, PLEASE and POWER strategies significantly affected the students’ competecy in writing across descriptive and recount text genres. The results imply the necessity to apply  PLEASE or POWER strategies when the Junior High School students write English text genres.